Infrastructure Construction Projects Scheduling Using Manual-Program Evaluation and Review Technique (M-PERT) Method. Case Study: Indonesian Sunda Strait Bridge - Ashadi, Reza Ferial; Husin, Albert Eddy; Guntorojati, Ireng (Jurnal Teknik Sipil, 2022)
Abstract The idea to build the Sunda Strait Bridge, popularly known as Jembatan Selat Sunda (JSS), began in the government of Indonesia's first president, Sukarno, which connect two islands with the largest economy in Indonesia, Sumatra Island and Java Island. This ambitious project will become a single mega infrastructure project with the largest investment in Indonesia. The successful completion of a project can be associated to the completion of a project on time. Accurate calculation of project time duration estimation is the key to the success of an infrastructure project delivery on time. Many practitioners in construction industry nowadays are having difficulties to estimates project duration correctly. Choosing the appropriate method in scheduling planning is the key to the successful estimation of a project. This research proposes the use of the M-PERT scheduling method which is the development of the conventional PERT with a higher degree of accuracy. As a case study, this research uses the Suspension Bridge section, which is one part of the overall phase of the construction of the JSS infrastructure project. The results of this research produce estimates of the project duration using M-PERT is 2104.38 days. It gives the estimation error is less than 1% when compared with the simulated curves. As a comparison, this research also calculates duration estimation using conventional PERT and it gives 2013 days with error more than 24% when compared with the simulated curves. A step-by-step process to estimate project duration using M-PERT method are also include in supplemental data. Keywords: Jembatan Selat Sunda, M-PERT, PERT, scheduling, simulated curves Abstrak Gagasan untuk membangun Jembatan Selat Sunda (JSS) dimulai pada masa pemerintahan presiden pertama Indonesia, Sukarno, yang menghubungkan dua pulau dengan ekonomi terbesar di Indonesia, Pulau Sumatera dan Pulau Jawa. Proyek ambisius ini akan menjadi mega proyek infrastruktur tunggal dengan investasi terbesar di Indonesia. Keberhasilan penyelesaian suatu proyek dapat dikaitkan dengan penyelesaian proyek tepat waktu. Perhitungan yang akurat dari estimasi durasi waktu proyek adalah kunci keberhasilan penyelesaian suatu proyek infrastruktur tepat waktu. Banyak praktisi di industri konstruksi saat ini mengalami kesulitan untuk memperkirakan durasi proyek dengan benar. Memilih metode yang tepat dalam perencanaan penjadwalan adalah kunci keberhasilan estimasi suatu proyek. Penelitian ini mengusulkan penggunaan metode penjadwalan M-PERT yang merupakan pengembangan dari PERT konvensional dengan tingkat akurasi yang lebih tinggi. Sebagai studi kasus, penelitian ini menggunakan bagian Jembatan Gantung yang merupakan salah satu bagian dari keseluruhan tahapan pembangunan proyek infrastruktur JSS. Hasil dari penelitian ini menghasilkan estimasi durasi proyek dengan menggunakan M-PERT adalah 2104,38 hari. Ini memberikan kesalahan estimasi kurang dari 1% jika dibandingkan dengan kurva yang disimulasikan. Sebagai perbandingan, penelitian ini juga menghitung estimasi durasi menggunakan PERT konvensional dan memberikan 2013 hari dengan error lebih dari 24% jika dibandingkan dengan kurva simulasi. Proses langkah demi langkah untuk memperkirakan durasi proyek menggunakan metode M-PERT diberikan dalam data tambahan. Kata-kata Kunci: Jembatan Selat Sunda, kurva simulasi, M-PERT, penjadwalan, PERT